2019
DOI: 10.3390/rs11030310
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Polycentric Urbanization Using Multisource Big Geospatial Data

Abstract: Understanding the dynamics of polycentric urbanization is important for urban studies and management. This paper proposes an analytical model that uses multisource big geospatial data to characterize such dynamics to facilitate policy making. There are four main steps: 1) main centers and subcenters are identified using spatial cluster analysis and geographically weighted regression (GWR) based on Visible Infrared Imaging Radiometer Suite (VIIRS)/NPP and social media check-in data; 2) the built-up areas are ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 38 publications
3
15
0
Order By: Relevance
“…Through the comparison, it was found that the two main centers in the plan were consistent with the experimental results in this paper: Yan'an Road and the area near West Lake on the north side of 3 Xiasha City Center…”
Section: Comparison Of Main Centers and Analysissupporting
confidence: 86%
See 1 more Smart Citation
“…Through the comparison, it was found that the two main centers in the plan were consistent with the experimental results in this paper: Yan'an Road and the area near West Lake on the north side of 3 Xiasha City Center…”
Section: Comparison Of Main Centers and Analysissupporting
confidence: 86%
“…(2) To use different data sources and threshold methods for comparative experiments and use population data to verify the accuracy quantitatively. (3) To compare the performance of our method with the evaluation report of the master plan.…”
Section: Study Areamentioning
confidence: 99%
“…At present, the data-centric [7,8] "smart city" is still in its infancy, and its development is challenged by none ective process of huge amount of data and restricted extraction of data values [9]. New technologies such as big data [6,10,11] processing, data mining, arti cial intelligence, and deep learning are important tools to build smart cities [6,12]. However, the analysis of geospatial data in many developed cities ignores some important social and economic management elements.…”
Section: Introductionmentioning
confidence: 99%
“…Various Internet map services such as Google Map, AMap, OpenStreetMap [50,67], and TianDiTu (IMap) can be directly connected to the BiGeo platform as reference data for a basemap service. Downloadable entity data, such as OSM data from OpenStreetMap [68][69][70], can also be opened, browsed, and queried directly in BiGeo. BiGeo can also publish managed data as a map service that complies with the OGC interface standard [29,71], and can mix and match these Internet map services.…”
Section: Toolkitmentioning
confidence: 99%